Écriture auto-ethnographique et positionnement: réflexivité entourant l’arabité et le queer - Bouqentar, Lamiae (Alterstice, 2021)
Cet article est un texte réflexif sur mon recours à une écriture auto-ethnographique dans ma recherche doctorale à propos de la migration arabe queer. En tant que chercheure arabe queer migrante, je puise dans la notion de positionnement, qui permet de considérer les expériences des groupes minorisés et racialisés comme une source pertinente de savoir. Inspirée de la tradition auto-ethnographique, je procède en incluant des fragments de récit de soi tirés de mes propres échanges de la vie, pour ainsi problématiser les identifications arabe et queer composant mon positionnement.
Keywords: 2000 à aujourd'hui; 2020-2029; LGBTQIA2+; afrique; amériques; approches et analyses; arts; autoethnographie; canada; communication; cours; discipline; féminisme décolonial; histoire et politique; intersectionnalité; maroc; montréal; premier cycle; périodes historiques; queer; québec; rabat; régions géographiques; sex2283; thématiques; études culturelles; études littéraires

Performing autobiography: Narrating a life as activism - Powell, Katrina M. (Palgrave Macmillan, 2021)
Performing Auto/biography: Narrating a Life as Activismanalyzes the rhetorical strategies employed in five authors' auto/biographical texts, examining their representations of identities and the public implications of writing individual identity. Exploring the ways race, class, culture, ethnicity, gender, and sexuality might affect the form(s) in which writers choose to write (e.g., memoir, fictional autobiography, poetry), questions how autobiographers challenge notions of genre, truth, and representation. This builds on the argument that constructing identity is a Performing Autobiography performance, one that can simultaneously use and subvert traditional notions of rhetoric and genre. By examining the auto/biographical texts of Zora Neale Hurston, Audre Lorde, Dorothy Allison, Joyce Johnson, and Shirley Geok-lin Lim together, the book theorizes self-representation and genres as rhetorical performances, and therefore their texts can be seen as "performative auto/biography"–transgressive archives where readers are asked to consider their own identities and act accordingly. In doing so, this book contributes to growing theories in feminist rhetorics and auto/biography studies, arguing that these performative genres advocate for life narratives as political and social activism.
Keywords: approches et analyses; archives; arts; autobiographie; discipline; histoire et politique; intersectionnalité; ressource en ligne; thématiques; études littéraires

Pauvreté: récits - Roussel, Stéphanie (Triptyque, 2021)
Ce livre est l'histoire de douze textes survivants, rescapés, qui, faute de ressources, auraient pu ne jamais voir le jour. Traversés par le thème de la pauvreté, ces récits troublent le rapport à la famille, à l'éducation, au corps, à la mode, à la nourriture, à la mémoire, à la dette ; les voix, éloquentes et poignantes, s'y font écho autant qu'elles adressent les silences qui persistent.
La nouvelle "Cuisine" de Marilou Craft a été donné à lire au cours LIT3495.
Keywords: approches et analyses; arts; cours; discipline; histoire et politique; intersectionnalité; inégalités; lit3495; pauvreté; point de vue situé; premier cycle; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Section: 1 volume (unpaged) : chiefly illustrations (some color) ; 26 cm
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Actualité de l’intersectionnalité dans la recherche féministe au Québec et dans la francophonie canadienne - Bourque, Dominique; Maillé, Chantal (Recherches féministes, 2015)
Introduction du numéro "Intersectionnalité" de la revue Recherches féministes, nov 2015.
Number: 2
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; har4600; histoire et politique; intersectionnalité; premier cycle; québec; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études féministes; études littéraires

This bridge called my back: Writings by radical women of color - Moraga, Cherríe; Anzaldúa, Gloria (SUNY Press., 2015)
merged in the last quarter of the twentieth century. Through personal essays, criticism, interviews, testimonials, poetry, and visual art, the collection explores, as coeditor Cherríe Moraga writes, the complex confluence of identities–race, class, gender, and sexuality–systemic to women of color oppression and liberation. Reissued here, forty years after its inception, this anniversary edition contains a new preface by Moraga reflecting on Bridge's living legacy and the broader community of women of color activists, writers, and artists whose enduring contributions dovetail with its radical vision. Further features help set the volume's historical context, including an extended introduction by Moraga from the 2015 edition, a statement written by Gloria Anzaldúa in 1983, and visual art produced during the same period by Betye Saar, Ana Mendieta, Yolanda López, and others, curated by their contemporary, artist Celia Herrera Rodríguez. Bridge continues to reflect an evolving definition of feminism, one that can effectively adapt to and help inform an understanding of the changing economic and social conditions of women of color in the United States and throughout the world.
Première édition 1981. Les textes "La Guëra" de Cherríe L. Moraga et « Lesbianism As an Act of Resistance » de Clark, Cherryl ont été donné en lecture au cours POL4212.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* de couleur; histoire et politique; intersectionnalité; lit3220; littérature; pol4212; pratiques féministes; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; témoignage; états-unis; études littéraires

Les filles en série: des Barbies aux Pussy Riot - Delvaux, Martine (Les éditions du remue-ménage, 2013)
Des corps féminins en rangées, qui se meuvent en synchronie. Ils ne se distinguent que par le détail d’un vêtement, d’une courbe, d’une teinte de cheveux. Les filles en série créent l’illusion de la perfection. Ce sont des filles-machines, filles-marchandises, filles-ornements. Toutes reproduites mécaniquement par l’usine ordinaire de la misogynie. Les filles sont des filles parce qu’elles sont en série. Mais la figure des filles en série est double: à la fois serial girls et serial killers de l’identité qu’on cherche à leur imposer. Entre aliénation et contestation, les filles en série résistent à leur chosification, cassent le party, libèrent la poupée et se mettent à courir. Cet essai percutant, paru pour la première fois en 2013, se déploie comme une chaîne qui se fait et se défait, depuis les Cariatides jusqu’aux Pussy Riot. Dans cette édition revue et augmentée, Martine Delvaux s’attaque à la blancheur des filles en série et analyse de nouvelles formes de résistance investies par les ballerines, les survivantes d’agressions et Beyoncé.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem3500; fem7000; histoire de l'art; histoire et politique; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit3220; militance; premier cycle; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Post-colonial studies: The key concepts - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 2000)
This volume provides an essential key to understanding the issues which characterise post-colonialism, explaining what it is, where it is encountered and why it is crucial in forging new cultural identities. As a subject, post-colonial studies stands at the intersection of debates about race, colonialism, gender, politics and language. In the language of post-colonial studies, some words are new, others are familiar words charged with new significance.
https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203449974
Keywords: approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; intersectionnalité; littérature; premier cycle; ressource en ligne; thématiques; études culturelles; études littéraires

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires